Is Southeast Asia's nuclear power ambition within reach? - Trajano, Julius Cesar Imperial (2024)
As governments in Southeast Asia find ways to achieve clean and secure energy systems, there is growing interest in the possibility that nuclear power, through advanced small reactors, will be the region’s source of clean energy in the future. However, they would first need to enhance their existing nuclear governance frameworks and mechanisms.